2017
DOI: 10.1093/jac/dkx263
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics and safety results from the Phase 3 randomized, open-label, study of intravenous posaconazole in patients at risk of invasive fungal disease

Abstract: ClinicalTrials.gov, NCT01075984.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 23 publications
1
34
0
6
Order By: Relevance
“…Very recently, PK and safety results from a phase 3 study of IV POS in patients at risk for invasive fungal disease were published. Six per cent of the patients had a steady‐state concentration between >2.5 and ≤3.65 mg/L without signs of toxicity . In a retrospective analysis of 64 patients receiving POS tablet as prophylaxis, median POS steady‐state concentrations of 1.67 mg/L (0.52‐3.83 mg/L) were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, PK and safety results from a phase 3 study of IV POS in patients at risk for invasive fungal disease were published. Six per cent of the patients had a steady‐state concentration between >2.5 and ≤3.65 mg/L without signs of toxicity . In a retrospective analysis of 64 patients receiving POS tablet as prophylaxis, median POS steady‐state concentrations of 1.67 mg/L (0.52‐3.83 mg/L) were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous doses above 300 mg were not investigated. The exposure of these two new formulations still shows substantial interpatient variability [31][32][33][34].…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%
“…Posaconazole exposure after administration of the oral suspension in healthy volunteers is about two to three times higher compared to hematological patients [42]. The steadystate exposures of posaconazole after administration of the delayed-release tablet or intravenous formulation are similar in patients with AML/MDS/HSCT, but are significantly higher than exposures achieved through administration of the suspension [32,34,[75][76][77]. The variability in posaconazole average concentration (C avg ) upon administration of the oral suspension in patients with AML/MDS/HSCT is relatively high, ranging from 57 to 68% [75,76].…”
Section: Posaconazole Descriptive Pharmacokineticsmentioning
confidence: 99%
“…Over the past few years, the therapeutic arsenal for invasive fungal infections (IFI) has expanded, especially for triazole antifungals. In addition to oral suspension, two new galenic formulations of posaconazole (POS) have been recently approved, consisting of a delayed‐release tablet and a powder for intravenous infusion . A new drug, isavuconazole (ISA), which is the active moiety of the water‐soluble prodrug isavuconazonium sulfate, is available in oral and intravenous forms for the treatment of mucormycosis and invasive aspergillosis .…”
Section: Introductionmentioning
confidence: 99%
“…The new tablet formulation makes it possible to reach higher POS C min values than for the oral suspension . This greater POS C min could theoretically result in a greater risk of side effects, although no study has yet clearly highlighted increased toxicity with the POS tablet formulation . Hence, no upper threshold for the POS C min has yet been proposed, even if some authors have suggested that dose reduction could be feasible for at least half of patients .…”
Section: Introductionmentioning
confidence: 99%